Population expansion and gene flow in Giardia duodenalis as revealed by triosephosphate isomerase gene - Seow Huey Choy; Mohammed A. K. Mahdy; Hesham M. Al-Mekhlafi; Van Lun Low; Johari Surin (Parasites & Vectors, 2015)
Abstract Background Giardia duodenalis is a protozoan parasite that can cause significant diarrhoeal diseases. Knowledge of population genetics is a prerequisite for ascertaining the invasion patterns of this parasite. In order to infer evolutionary patterns that could not be uncovered based on the morphological features, a population genetic study with the incorporation of molecular marker was carried out to access the genetic structure of G. duodenalis isolated from the Malaysian population and the global populations. Methods A total of 154 samples positive for Giardia, collected from different Malaysian communities, were subjected to DNA amplification and sequencing targeting three genetic loci (tpi, gdh, and bg). The tpi sequences together with sequences from the global data obtained from the NCBI GenBank were used for genetic diversity analyses including identification of haplotypes, haplotype diversity, nucleotide diversity, Tajima’s D and Fu and Li’s D, gene flow and genetic differentiation tests. Results Analysis of the Malaysian and global data showed that assemblages A, B, and E (the most prevalent assemblages in humans and animals), have different levels of genetic diversity. Assemblage B had the highest level of both haplotype diversity and nucleotide diversity, followed by assemblage E. The analysis also revealed population expansion and high gene flow in all assemblages. No clear genetic structure was observed across five continents (i.e., the Americas, Europe, Asia, Australia and Africa). However, median joining network of assemblage B formed a cluster that was exclusively isolated from Asia while other haplotypes were well dispersed across the continents. Conclusions This study provides new insight into the genetic diversity of Giardia assemblages in different geographical regions. The significant result shown by gene flow and genetic differentiation analyses as well as test of neutrality among the populations should have brought a clearer picture to the dynamics and distribution of Giardia infection.